Determinants of Dividend Policy in Selected Indian Industries: An Empirical Analysis - Sudhahar, M. (Indian Journal of Finance, 2010)
The present study is an attempt to identify the factors that might be important in determining the dividend policy decision for the managers of the Indian companies. The regression analysis technique has been adopted and analysis are carried out for each industry and each size classes to identify the factors affecting corporate dividends with the help of some known dividend models such as Lintner’s Model, Brittain’s Cash Flow Model, Brittain’s Explicit Depreciation Model and Darling’s Model. The period of the study is for 10 years from 1997-98 to 2006-07. The study is explorative in nature and based on secondary data. The data for the study consists of various financial statements of selected companies listed in the Bombay Stock Exchange (BSE) under Group A and B. It is found that paying dividend to shareholders in Indian companies is positively determined by last year dividend, current year profit after tax and negatively by current year depreciation.